The Effect of Menu Diversity, Location and Price on Consumer Buying Interest at Cindy Kwala Begumit Rice Shop - Putri, Cindy Melati; ,, Erwansyah; Agustin, Roro Rian (Universitas Negeri Medan, 2024)
This study aims to analyze the influence of menu diversity, location and price on consumer buying interest. The location of the research was carried out at the Cindy Kwala Begumit Rice Shop. The sample of this study is 100 respondents who are consumers of the Cindy Rice Shop. The method used is multiple linear regression analysis with processing assisted by SPSS Software v 25. The results of the study show that partially Menu Diversity (X1) has a significant positive influence on Consumer Buying Interest. Location (X2) has a significant positive influence on Consumer Buying Interest. Price (X3) has a significant positive influence on Consumer Buying Interest. Meanwhile, simultaneously Menu Diversity (X1), Location (X2) and Price (X3) have a significant positive influence on Consumer Buying Interest.